PENGEMBANGAN SOAL MATEMATIKA MODEL PISA KATEGORI FORMULATE UNTUK PESERTA DIDIK SMP/MTS - Satiti, Wisnu Siwi; Dwi Agustina, Sherly Sabrela (JoEMS (Journal of Education and Management Studies), 2021)
Mathematics learning should not only emphasize on computational algorithms, but focus on mathematical-thinking-skills, reasoning and critical-thinking. Mathematical activity that is able to accommodate this, as well as facilitate students to apply mathematical-concepts they have mastered to solve problems from real-life situations, is PISA-like mathematics-problems. This mathematics-problems emphasizes on mathematical literacy. Mathematical literacy is an individual's capacity to formulate, employ, and interpret mathematical solutions obtained into the real-life context provided. However, based on the results of several previous studies, it is known that many students have difficulty working on PISA-like mathematics-problems, one of which is in formulate. Therefore, it is necessary to increase the use of PISA-like mathematics-problems as mathematics learning activity at schools. Thus, in this study, it is developed the PISA-like mathematics-problems on Formulate category. This study employs Research and Development (R&D) method with the ADDIE model. The results of the product trial show that the product developed is valid and gets a response with "Good" criteria from students. In addition, through working on the PISA-like mathematics-problems developed, it helps students understand relationship between mathematics and real-life phenomena. It also demonstrates that mathematical abilities are needed and used in a variety of real-life situations.